قرآنِ کریم کے مناہجِ تدریس اور جدید طریقِ تدریس میں اُن کے مظاہر کا تنقیدی مطالعہ: A Critical Study of the Teaching Methodologies of the Holy Qur’an & Their Manifestations in Modern Pedagogical Approaches - Muḥammad Qayyūm Khān; Dr. Manzoor Aḥmad (Al-Amīr Research Journal for Islamic Studies, 2025)
The Qur’an serves as a comprehensive code of life, providing complete guidance for humanity in every sphere, including education. It emphasizes the acquisition of knowledge and intellectual development as the foundation of human progress. The first revelation itself begins with the command to “read,” symbolizing the centrality of learning in Islam. Throughout the Qur’an, prophets are presented as teachers of mankind, from Adam to Muhammad (peace be upon him), each fulfilling the divine responsibility of guiding people through knowledge and moral instruction. This research article explores the educational philosophy and teaching methodologies reflected in the Qur’an and examines their relevance to modern pedagogical practices. The study identifies several key methods used in Qur’anic instruction such as dialogue, questioning, storytelling, reasoning, and experiential learning and analyzes how these techniques align with contemporary theories of active and reflective learning. Findings suggest that the Qur’anic model of teaching not only promotes intellectual growth but also emphasizes moral and spiritual development, creating a holistic educational framework. The research concludes that the Qur’an offers timeless pedagogical principles that can serve as a guiding source for teachers, scholars, and curriculum designers in modern education systems. Keywords: Qur’anic Pedagogy, Teaching Methods in the Qur’an, Islamic Education, Modern Pedagogy, Knowledge in Islam